Natural genetic variation for grapevine phenology as a tool for climate change adaptation - van Houten, Silvina (2020)
Grapevine phenology is being modified by climate change, particularly by the increase of temperatures that affect grape attributes for wine production. Besides the existing oenological and viticultural approaches, the thorough exploration of the current intra-cultivar genetic variability to select late-ripening genotypes emerges as an interesting alternative. In the present work, we have analyzed the natural genetic variation for phenology and agronomic traits among 21 'Malbec' clones and we demonstrated that fruiting cuttings are a useful tool for the analysis of such variation in 'Malbec'. Several clones could be distinguished by agronomic traits like berry number or cluster weight, and mainly by phenology characteristics like the length of the phase between flowering and veraison, which reached more than 16 days between early and late clones. These results support the approach of exploring grapevine clone collections in searching for genotypes with delayed phenology, and thus with the potential to maintain some expected quality characteristics under warm conditions.